Analisis Pengaruh Dana Pihak Ketiga, CAR, LDR, dan Inflasi Terhadap Return On Assets Pada Bank Umum di Indonesia - Gladys Aqilla Pramita Nugraha; Riko Setya Wijaya (CV. Ulil Albab Corp, 2022)
Development of the economic system in this modern era, make banks as business entities or institutions in the field of finance to concentrate to their financial performance as measured by Return On Assets (ROA) in order to support all bank activities to encourage economic growth. This study proposed to determine the effect of Third Party Funds (DPK), CAR, LDR, and Inflation on Return On Assets at Commercial Banks in Indonesia. This Study used quantitative methods. The data were analyzed by using descriptive statistic. This study used multiple Linear Regression Analysis used the SPSS 20 Application with an observation period for about thirteen years (2008 – 2020). The result of this study indicated that Third Party Funds (DPK) had not significant effect on Return On Assets, CAR had a significant effect on Return On Assets, LDR had a significant effect on Return On Assets, and Inflation had not significant effect on Return On Assets.